Association between diabetic nephropathy and other diabetic microvascular and macrovascular complications - Chandy Anila; Pawar Basant; John Mary; Isaac Rajesh (Saudi Journal of Kidney Diseases and Transplantation, 2008)
Diabetic nephropathy is found to be significantly associated with diabetic retino-pathy and coronary artery disease. Few studies have also shown an association between diabetic nephropathy and neuropathy, and peripheral vascular disease. A cross sectional study was done among consecutive type 2 diabetics presenting to Christian Medical College and Hospital, Ludhiana from June 2004 to May 2005. Patients were subjected to the clinical and laboratory investigations 174 patients were studied over a period of one year. Diabetic nephropathy was found to be associated with proliferative diabetic retinopathy, neuropathy and cardiovascular disease by univariate analysis. In multivariate analysis, diabetic nephropathy was again significantly asso-ciated with proliferative diabetic retinopathy and coronary artery disease. We conclude that close association between diabetic nephropathy and other micro and macrovascular complications exists in our Indian patients also.